A Nestin–Cyclin-Dependent Kinase 5–Dynamin-Related Protein 1 Axis Regulates Neural Stem/Progenitor Cell Stemness via a Metabolic Shift. (22nd January 2018) - Wang, Jiancheng; Huang, Yinong; Cai, Jianye; Ke, Qiong; Xiao, Jiaqi; Huang, Weijun; Li, Hongyu; Qiu, Yuan; Wang, Yi; Zhang, Bin; Wu, Haoxiang; Zhang, Yanan; et al.
Abstract : Neural stem/progenitor cells (NSPCs) transplantation provides an alternative approach for various central nervous system (CNS) diseases treatment, while the difficulties in NSPC acquisition and expansion limit their further application. Unveiling the mechanism of NSPC stemness regulation may contribute to its further application. Nestin, generally recognized as a marker of NSPCs, plays a crucial role in the CNS development and NSPC stemness maintenance. Here, we report that Nestin loss triggers mitochondrial network remodeling and enhances oxidative phosphorylation (OXPHOS) in NSPCs treated with Nestin RNA interference (RNAi). Mitochondrial morphology is dynamically controlled by the balance between fission and fusion mediators; one of these mediators, the pro-fission factor, dynamin-related protein 1 (Drp1), shows decreased activation in Nestin-knockdown cells. Upstream, Drp1 phosphorylation is under control of the cytosolic cyclin-dependent kinase 5 (Cdk5). Inhibition of Cdk5 using RNAi or a chemical inhibitor (roscovitine) induces mitochondrial elongation and promotes mitochondrial respiration, indicating that Cdk5-dependent Drp1 phosphorylation participates in mitochondrial metabolism and NSPC stemness regulation. Strikingly, Nestin knockdown results in Cdk5 redistribution, with less remaining in the cytosol, leading to mitochondrial remodeling. We identify Nestin1-640 sequesters Cdk5 in the cytosol and phosphorylates Drp1 subsequently. Together, our results show that a Nestin-Cdk5-Drp1 axis negatively regulates mitochondrial OXPHOS, which is indispensable for the maintenance of NSPC stemness. Abstract : Nestin regulates the self-renewal and proliferation properties of neural stem/progenitor cells (NSPCs) through influencing mitochondrial dynamics and metabolism phenotypes. RNAi-mediated Nestin knockdown induces a decrease of Cdk5 sequestered in the cytosol. Consequently, Drp1 phosphorylation mediated by cytosolic Cdk5 is repressed, resulting in mitochondrial elongation, enhanced OXPHOS and compromising stemness of NSPCs.